Fabrication, Electrical Characterization and Simulation of Thin Film Solar Cells: CdTe and CIGS Materials - Es'haghi Gorji, Nima <1984> (Alma Mater Studiorum - Università di Bologna, 2014)
CdTe and Cu(In,Ga)Se2 (CIGS) thin film solar cells are fabricated, electrically characterized and modelled in this thesis. We start from the fabrication of CdTe thin ﬁlm devices where the R.F. magnetron sputtering system is used to deposit the CdS/CdTe based solar cells. The chlorine post-growth treatment is modiﬁed in order to uniformly cover the cell surface and reduce the probability of pinholes and shunting pathways creation which, in turn, reduces the series resistance. The deionized water etching is proposed, for the ﬁrst time, as the simplest solution to optimize the effect of shunt resistance, stability and metal-semiconductor inter-diffusion at the back contact. In continue, oxygen incorporation is proposed while CdTe layer deposition. This technique has been rarely examined through R.F sputtering deposition of such devices. The above experiments are characterized electrically and optically by current-voltage characterization, scanning electron microscopy, x-ray diffraction and optical spectroscopy. Furthermore, for the ﬁrst time, the degradation rate of CdTe devices over time is numerically simulated through AMPS and SCAPS simulators. It is proposed that the instability of electrical parameters is coupled with the material properties and external stresses (bias, temperature and illumination). Then, CIGS materials are simulated and characterized by several techniques such as surface photovoltage spectroscopy is used (as a novel idea) to extract the band gap of graded band gap CIGS layers, surface or bulk defect states. The surface roughness is scanned by atomic force microscopy on nanometre scale to obtain the surface topography of the ﬁlm. The modiﬁed equivalent circuits are proposed and the band gap graded profiles are simulated by AMPS simulator and several graded proﬁles are examined in order to optimize their thickness, grading strength and electrical parameters. Furthermore, the transport mechanisms and Auger generation phenomenon are modelled in CIGS devices.